Zakat Produktif dan Kesejahteraan Ummat: Menelisik Program Riau Makmur Melalui Badan Amil Zakat Nasional Riau - Syahrizal, Syahrizal; Alhidayatillah, Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to find out the productive zakat in the welfare of the ummah carried out by the Riau National Amil Zakat Agency with the implementation of corn plantations in Karya Indah Village, Tapung District. This study uses a qualitative descriptive method and the data collection techniques used are observation, interviews and documentation. The results of the study show that productive zakat is carried out by the Riau National Amil Zakat Agency through several indicators in the purpose of utilizing productive zakat. The first indicator is that zakat funds are given to mustahik as a model of productive business assistance. The author found that the Riau National Amil Zakat Agency provides capital in the form of money to be purchased for the needs and needs of corn plantations. Second, productive zakat is carried out by mustahik coaching. The author found that the coaching carried out is to provide an understanding of the way, enthusiasm and encouragement in working in terms of production.